Cellulose nanofiber grafting and aluminum nitride deposition on the surface of expanded graphite to improve the thermal conductivity and mechanical properties of phase change material composites. (1st February 2022) - Lee, Wondu; Kim, Jooheon
Abstract: Phase change material (PCM) composites have attracted much attention as thermal energy storage devices for thermal management because of their high latent heat. However, the intrinsically low thermal conductivity of PCMs hinders the efficient thermal management of these devices. In this study, novel cellulose nanofibers (CNFs) grafting onto an expanded graphite (EG) and aluminum nitride (AlN) covering were carried out to prepare novel thermally conductive PCM composites, analyzed in detail using Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), Raman spectra, X-ray diffraction (XRD) patterns, field-emission scanning electron microscopy (FE–SEM), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The composites exhibited ultra-high through-plane thermal conductivity of 3.39 W/mK and latent heat of 136 J/g, and the tensile strength increased by 402% compared with pure erythritol. The resulting erythritol/EG–CNF/AlN composites enable efficient thermal management because they save and dissipate heat due to the high latent heat and thermal conductivity. Moreover, the composite was insulated by nano-size AlN covered on the surface and pores of the EG structure. The proposed PCM composites are promising candidates for developing superior thermally conductive PCM composites and advanced electronic packaging. Graphical abstract: Image 1 Highlights: The CNF grafted EG reinforced properties of Erythritol PCM composites. The AlN covering on the surface of EG-CNF formed heat transfer paths. The freeze-casting method prevented deterioration of properties of Erythritol.